SINTESIS SILIKA MESOPORI TERSULFONASI DARI ABU SEKAM PADI (Oryza sativa L.) - Maylina, Ajeng Chandra; Subagyono, R.R. Dirgarini Julia Nurlianti; Daniel, Daniel (JURNAL ATOMIK; Vol 3 No 2 (2018), 2018)
A study on the synthesis of sulphonated mesoporous silica from rice husk ash ( Oryza sativa L. ) been conducted. The preparation of sulphonated MSU-H was conducted by several steps namely, extraction of silica from rice husk ash, synthesis of mesoporous silica, synthesis of sulphonated mesoporous silica with post-grafting method. The N 2 adsorption-desorption characterization results show the surface area of mesoporous silica 134 m 2 /g, pore volume 0.81 cm 3 /g and pore size 24.13 nm. The FT-IR characterization results of sulphonated mesoporous silica indicate the presence of Si-O-Si, Si-O, O-H and C-H alkane clusters.